Experimentation: A Gestalt Approach to Counselling - Greenberg, Leslie S.; Kahn, Sharon E. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper describes the "experiment", a Gestalt approach to stimulating client awareness. The authors present examples of experiments which may be used to facilitate the client in trying on new ways of being. To clarify the roles of the counsellor and client in the experiment and to describe the process and goals of the method, the authors contrast the experiment with behavioural rehearsal. Gestalt principles and theory are explained. Promoting client involvement through the experiment requires the active participation of the counsellor and leads to the development of new understanding for the client.